Clinicopathological correlations in heart transplantation recipients complicated by death or re-transplantation - McDonald, Michelle M.; Mihalj, Maks; Zhao, Bihong; Nathan, Sriram; Matejin, Stanislava; Ottaviani, Giulia; Jezovnik, Mateja K.; Radovancevic, Rajko; Kar, Biswajit; Gregoric, Igor D.; Buja, L. Maximilian (Frontiers in Cardiovascular Medicine, 2022)
Purpose: This study aimed to identify and correlate pathological findings with clinical outcomes in patients after orthotopic heart transplantation (OHT) who either died or underwent a re-transplantation. Methodology and Study Design: Single-center retrospective analysis of primary OHT patients who died or were re-transplanted between Oct 2012 and Jul 2021. Clinical data were matched with corresponding pathological findings from endomyocardial biopsies on antibody-mediated rejection, cellular rejection, and cardiac allograft vasculopathy. Re-assessment of available tissue samples was performed to investigate acute myocardial injury (AMI) as a distinct phenomenon. These were correlated with clinical outcomes, which included severe primary graft dysfunction. Patients were grouped according to the presence of AMI and compared. Results: We identified 47 patients with truncated outcomes after the first OHT. The median age was 59 years, 36 patients (76%) were male, 25 patients (53%) had a prior history of cardiac operation, and 21 patients (45%) were supported with a durable assist device before OHT. Of those, AMI was identified in 22 (47%) patients (AMI group), and 25 patients had no AMI (non-AMI group). Groups were comparable in baseline and perioperative data. Histopathological observations in AMI group included a non-significant higher incidence of antibody-mediated rejection Grade 1 or higher (pAMR ≥ 1) (32% vs. 12%, P = .154), and non-significant lower incidence of severe acute cellular rejection (ACR ≥ 2R) (32% vs. 40%, P = .762). Clinical observations in the AMI group found a significantly higher occurrence of severe primary graft dysfunction (68% vs. 20%, p=0.001) and a highly significant shorter duration from transplantation to death or re-transplantation (42 days [IQR 26, 120] vs. 1133 days [711-1664], P < .0001). Those patients had a significantly higher occurrence of cardiac-related deaths (64% vs. 24%, P = .020). No difference was observed in other outcomes. Conclusions: In heart transplant recipients with a truncated postoperative course leading to either death or re-transplantation, AMI in endomyocardial biopsies was a common pathological phenomenon, which correlated with the clinical occurrence of severe primary graft dysfunction. Those patients had significantly shorter survival times and higher cardiac-related deaths. The presence of AMI suggests a truncated course after OHT.